Port performance in Asia: Does economic efficiency imply environmental efficiency - CHIN, Anthony T. H. (Institutional Knowledge at Singapore Management University, 2010)
Atmospheric and water pollution are two main sources of negative environmental externalities generated by shipping. This study recognizes the negative externalities in the production of port services in East Asia by explicitly incorporating environmental impacts of shipping. Programming techniques are used to analyze 156 Origin–Destination pairs between 13 major East Asian ports, to derive the externality-augmented measures of port productivity and efficiency at the waterside. The results suggest that the inclusion of externality mitigation strategies can exert a considerable influence on efficiency performance.